2003
DOI: 10.1063/1.1568527
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced defects in KTaO3

Abstract: Photoconductivity (PC), thermally stimulated conductivity (TSC), photoluminescence (PL), thermoluminescence (TL), and electron spin resonance (ESR) measurements have been made on single crystals of potassium tantalate over the temperature range 4.2–290 K. We revealed two sorts of O− shallow hole centers which are responsible for the two temperature regions of PL and PC enhancement: T<70 K and 100–150 K. Both O− centers were identified by their ESR spectra. While at low temperatures PL and PC have a rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…[1][2][3] Recently, the luminescence properties have been extensively studied in many ABO 3 perovskite structures ͑A = Sr, Ba, K, etc., B = Nb, Ti, Ta, etc.͒, and this has provided information on the photochemical properties of ABO 3 perovskites, such as photocatalysis, photoinduced electron-transfer dynamics, and excitation energy transport. [2][3][4][5] These ABO 3 perovskites exhibit a broad emission band with a large Stokes shift at low temperatures, whereas the luminescence is usually quenched at high temperatures and it is hard to detect at room temperature. Several mechanisms for the luminescence properties of ABO 3 perovskites have been proposed.…”
mentioning
confidence: 99%
“…[1][2][3] Recently, the luminescence properties have been extensively studied in many ABO 3 perovskite structures ͑A = Sr, Ba, K, etc., B = Nb, Ti, Ta, etc.͒, and this has provided information on the photochemical properties of ABO 3 perovskites, such as photocatalysis, photoinduced electron-transfer dynamics, and excitation energy transport. [2][3][4][5] These ABO 3 perovskites exhibit a broad emission band with a large Stokes shift at low temperatures, whereas the luminescence is usually quenched at high temperatures and it is hard to detect at room temperature. Several mechanisms for the luminescence properties of ABO 3 perovskites have been proposed.…”
mentioning
confidence: 99%
“…When increasing the temperature from 4.3 to 20 K, the thermal hopping process starts to be activated. The photocurrent reported by several authors in KTaO 3 [11,14] should be due to such thermal hopping and tunneling of the carriers.…”
Section: Resultsmentioning
confidence: 92%
“…The origins have been attributed to the STEs or the oxygen vacancies that also induce a strongly relaxed exciton luminescence [9]. In KTaO 3 , it has been revealed that the luminescence related to oxygen vacancies appears around 2.05 eV [9][10][11]. In Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The position in the NIR and the large half width of the light-induced and reduction-induced absorption bands also indicate the polaronic nature of the defects created. Hole polaron centers, like two different sorts of O -centers, were revealed in recent EPR work [13,14]. Electron polarons Ta 4+ in KTaO 3 [15] are not confirmed yet, but similar electron polarons (Ti 3+ in BaTiO 3 and Nb 4+ in LiNbO 3 ) have been determined experimentally [16,17].…”
Section: Discussionmentioning
confidence: 96%